2002
DOI: 10.5694/j.1326-5377.2002.tb04549.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone and cefotaxime use in Victorian hospitals

Abstract: Objective: To determine patterns of use of ceftriaxone and cefotaxime (CEFX) in Victorian hospitals and to identify areas for improvement. Design, patients and setting: A concurrent, observational evaluation of CEFX use in patients commencing a course of these drugs between 8 and 14 September, 1999, in 51 Victorian hospitals. Main outcome measures: Proportion of patients treated with CEFX; indications; duration of use; concordance with recommendations of national antibiotic guidelines (Therapeutic guidelines: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 5 publications
2
27
1
Order By: Relevance
“…In this study, 114 patients (16%) satisfied these criteria; however, 44% of patients were prescribed ceftriaxone or cefotaxime. This result is consistent with previous Australian studies, which also demonstrated a high level of third‐generation cephalosporin use outside Guidelines recommendations 12 , 20 …”
Section: Discussionsupporting
confidence: 93%
“…In this study, 114 patients (16%) satisfied these criteria; however, 44% of patients were prescribed ceftriaxone or cefotaxime. This result is consistent with previous Australian studies, which also demonstrated a high level of third‐generation cephalosporin use outside Guidelines recommendations 12 , 20 …”
Section: Discussionsupporting
confidence: 93%
“…It is interesting to note that twice‐daily administration accounted for 76.9% of the cases and at the same time, frequency of administration was found to be the leading cause of inappropriate ceftriaxone use which is observed in 78.3% of the cases. This finding was similar in the study done in Addis Ababa and USA …”
Section: Discussionsupporting
confidence: 91%
“…In our study, the prevalence rate of use of 3GCs was lower than the reported rate of 43 per 1000 admissions for ceftriaxone in 51 Victorian Hospitals in Australia of which 82% was prescribed as empirical treatment [19]. Our data reveals extensive overall inappropriate use of these drugs (62%) at the POSGH in Trinidad, with a rate that is higher than an earlier literature report (31%) [20].…”
Section: Discussioncontrasting
confidence: 67%